2007
DOI: 10.1785/0120050161
|View full text |Cite
|
Sign up to set email alerts
|

Late Holocene Paleoseismicity of the Southern Part of the Chelungpu Fault in Central Taiwan: Evidence from the Chushan Excavation Site

Abstract: The geomorphic expression of the frontal Western Foothills in central Taiwan is usually defined by a late Holocene scarp that ranges from tens to hundreds of meters in height. This scarp is the product of displacement on a near-surface 20-30Њ east-dipping thrust fault, the Chelungpu fault, which ruptured during the Chichi earthquake. The large scarp height may correspond directly to the accumulation of successive surface ruptures. The Chushan site is located on the southern part of this fault where the Chichi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 27 publications
0
40
1
Order By: Relevance
“…Over the past ten years, we have excavated numerous sites and continuously cored borings on the Chelungpu fault, where the surface rupture shows surface deformation within the Holocene deposits; our results have provided quantitative data for late Holocene slip rates ( Fig. 1; Chen et al, 2001aChen et al, , b, 2004Chen et al, , 2007aOta et al, 2001Ota et al, , 2005Streig et al, 2007). Bedrock exposed along the Shihkang fault has not been characterized in previous paleoseismic studies.…”
Section: Paleoseismologic Analysismentioning
confidence: 87%
“…Over the past ten years, we have excavated numerous sites and continuously cored borings on the Chelungpu fault, where the surface rupture shows surface deformation within the Holocene deposits; our results have provided quantitative data for late Holocene slip rates ( Fig. 1; Chen et al, 2001aChen et al, , b, 2004Chen et al, , 2007aOta et al, 2001Ota et al, , 2005Streig et al, 2007). Bedrock exposed along the Shihkang fault has not been characterized in previous paleoseismic studies.…”
Section: Paleoseismologic Analysismentioning
confidence: 87%
“…For example, in the Chelungpu fault rupture cases, the north segment had not ruptured independently according to the paleo-earthquake results using trenching data (Chen et al 2007), so this article gave the north segment a lower weight than the south segment as well as the entire fault. In the TamaopuShuangtung fault rupture cases, because the length of the Tamaopu fault segment is too short to induce a large earthquake, this article gave 0.1 as the weight for the Tamaopu fault segment.…”
Section: Fault Segmentationmentioning
confidence: 94%
“…supports the idea that the reoccurring ruptures on a fault can be described by a time-predictable model. The conclusion from paleoseismological investigations in Taiwan indicated that the behavior of rupture episodes at active faults adhere to a time-predictable model, based on a consistent slip rate level at which the earthquake occurs, such as the Chelungpu fault (Chen et al 2004(Chen et al , 2007 or the Longitudinal Valley fault (Yen et al 2008) etc. (as shown in Fig.…”
Section: The Paleoseismological Investigation In Taiwanmentioning
confidence: 95%
“…Seven trenches were excavated along this fault to investigate the history of large earthquake events. (Chen et al 2007; http:// cgsweb.moeacgs.gov.tw/). The average slip rate of the Chelungpu fault is 6.4 mm yr -1 .…”
Section: The Paleoseismological Investigation In Taiwanmentioning
confidence: 99%
See 1 more Smart Citation